Opportunities and Threats to Learning: Lessons from a Pedagogical Workshop for Faculty at a Higher Education Institution - Namubiru Ssentamu, Proscovia (Journal of Education and Training Studies, 2014)
Faculty quality is a key variable in the quality of teaching and learning. However, although learning is the basis for teaching, the circumstances under which faculty learn largely remain unexplained. This paper focuses on the opportunities and threats to learning by faculty at Uganda Management Institute (UMI). The paper is based on a study of the evaluations completed by faculty at a pedagogical workshop organised to strengthen their teaching knowledge, skills and attitudes. A case study confirmatory research design was used to identify and analyze the opportunities and threats affecting learning based on the theories of constructivism, social constructivism and the principles of adult learning. Findings confirm that learning opportunities and threats are dependent on the degree of support from significant others, the content, methods and environment (Reigeluth & Carr-Chellman, 2009; Aldridge & Fraser, 1999; Seaman & Fellenz, 1989). Faculty were more critical of the strengths and weaknesses of the facilitators, methods and environment than they were of the content and of themselves as learners. The evaluation of the former focused on the conduct and management of these constructs than on the constructs themselves. Limited self-reflection and criticism could be viewed from a wider Ugandan cultural perspective. Whereas the teaching of content could be evaluated differently, content itself is a context-independent variable, and therefore a stable phenomenon (Ssentamu, 2010). Based on the findings, higher education institutions could holistically focus on colleagues, facilitators, content, methods and environment as key constructs in enhancing faculty learning both at strategic and operational levels.
Keywords: Pedagogy; Adult learning; Learning environment; Evaluation; Faculty; Higher education.higher education